Analysis of improvement ways of creative accounting - I.A. Yuhimenko-Nazaruk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The necessity of carrying out the research in the direction of finding out the ways to improve creative accounting is grounded. The existing approaches of researchers to eliminate the negative consequences of creative accounting are analyzed. Four main groups of researchers' approaches to the improvement of creative accounting are singled out and analyzed. The general and distinctive features of the researchers’ proposals on the improvement of creative accounting are examined. The reasons for the impossibility of using the ethical approach to the improvement of creative accounting in Ukraine in modern conditions are grounded. The necessity of procedural aspects perfection of the creative accounting on the basis of the concept of true and fair view is proved. The classification of the approaches to the construction of accounting methodology in the context of the use of creative accounting is developed. The main regulations of the concept of true and fair view are studied, their use provides an adequate reflection of the company's economic reality in financial reporting.